DEVELOPMENT MECHANISMS OF INNOVATIVE COOPERATION IN ENSURING EDUCATIONAL EFFICIENCY - Ochilova Gulnoza Odilovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The issues of the development of the innovation market in the sphere of education are discussed, foreign experience in the development of innovative corporate communications in the sphere of education is analyzed, questions about the main ways of development of innovative corporate communications in the education sphere are studied, materials on the ways of developing the quality of education through innovative corporate communications in the system "Science-education-production". Also, in the scientificarticle, recommendations were developed for the development of innovative corporate communications in the field of education.